Vivências das famílias de crianças com autismo durante a pandemia da covid-19. - Lopes, Jessica Fernandes (2024)
With the COVID-19 pandemic and the social distancing measures adopted to reduce the spread of the virus, children and adolescents with ASD have been considered one of the social groups most impacted during this period, due to the clinical characteristics of the condition, the difficulty in understanding the current situation, in adapting to changes, especially in the context of routine.Therefore, this research aimed to understand the experiences of families of children with ASD during the COVID-19 pandemic in the municipality of Sobral, Ceará, Brazil. This is an exploratory-descriptive research, with a qualitative approach developed with 17 guardians of families of children with ASD living in an interior municipality of Ceará, based on a semi-structured interview from June to August 2023. Analysis of information occurred through content analysis by Bardin (2011). The research was approved by the Research Ethics Committee of the Universidade Estadual Vale do Acaraú, following the principles established by Resolution 466/12, of the National Health Council. The results were grouped into four categories of analysis, which, in turn, , are divided into analysis subcategories. The analytical category: 1) Feelings experienced by families of children with ASD, the following subcategory emerged: a) Emotional and psychological experiences. Category 2) Repercussions of the pandemic in the family context, had the following subcategories: a) Behaviors of children with ASD during the COVID-19 pandemic; b) Daily impacts on the care of children with ASD during the pandemic. Category 3) Coping strategies adopted by families had the following subcategories: a) Playful resources and stimulation activities at home to promote the well-being of children with ASD; and b) Support network: involvement of family members or caregivers in caring for children with autism during the pandemic. And category 4) Health care and education for children with ASD during the pandemic, had the following subcategories: a) Impact of pandemic restrictions on the continuity of health services for children with ASD; and b) Repercussions of the pandemic on the learning process of children with ASD. Firstly, the feelings experienced during the pandemic were evident, such as anxiety, fear, isolation, despair, anguish, insecurity and concern for the health and well-being of their children, in addition to financial issues, the fear of dying, the fear of losing loved ones and fear of the future.The experience of families of children with ASD in times of pandemic was permeated by many challenges, including the interruption of support services and therapies, the need to adapt to new routines and the impact of social isolation on the behavior and development of your children. The families demonstrated a lot of strength and resilience through their reports, just as we can also see several vulnerabilities during the pandemic. The research also seeks to encourage future studies on post-pandemic consequences, as it will allow the implementation of new care strategies for families and children with ASD according to their needs.